ON THE BOREL THEOREM - Haggui, Fathi; Jalled, Abdessami (Matematichki Bilten, 2021)
In this note we give a new characterization of holomorphic curves which lies in the complement of \(2n\) hyperplanes in general position. This is a generalisation of The Borel Theorem. By M.Green, any holomorphic curves which lies in the complement of \(2n + 1\) hyperplanes in general position is constant. Using our generalisation of The Borel Theorem, we can easily show Green’s Theorem.